Dimension and Illusion Of Contemporary Art - I Made Suarpradana, K; Muka, I Ketut; Sida Arsa, I Ketut (Jurnal Pendidikan Seni Rupa Undiksha, 2025)
The duality that refers to dimensions and illusions becomes an interest in creating a unified work. Dimensions and illusions have different meanings from each other. Dimensions have space (length, width and height) while illusions (optical art) can only be enjoyed from one side (front view). Basic things like this can be developed into various visuals. The output produced by illusions and dimensions complement each other, as dimensions can produce illusions of what is seen, and vice versa, illusions can produce space or dimensions due to the influence of colors and lines. The work of creating this thesis combines the two concepts (dimensionality and illusion) into a unified work. Knowing the weakness of the sense of sight in capturing an object, it seems to be of particular interest if you succeed in realizing a work that has a convex volume that appears concave, or conversely that a concave object appears convex. The basic reason for this creation was to explore the basic elements of fine art into contemporary works of art. It is also hoped that it can provide wider knowledge to the public regarding ideas that cross the boundaries of fine art conventions.